Italian crime fiction between postmodern impegno and moral rebellion - Paoli, Marco (Incontri. Rivista europea di studi italiani, 2014)
Review of: Politics and Society in Italian Crime Fiction: An Historical Overview by Barbara Pezzotti, Jefferson North Carolina, McFarland & Company, 2014, 234 pp., ISBN 9780786476527, € 32.46 / £ 30.56 / $ 40.00 (paperback).